2020
DOI: 10.1016/j.ibror.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of levomepromazine on the healthy and injured developing mouse brain – An in vitro and in vivo study

Abstract: Highlights Levomepromazine (LMP) does not induce cell death in the healthy developing brain. Excitotoxic lesion size and apoptosis are unaffected by LMP. Body weight gain is reduced in mouse pups receiving higher-dose LMP treatment. Further studies are required prior to a routine use of LMP in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…It is reported that NAC has a protective effect against oxidative damage by regulating the Nrf2/HO-1 signal activated by oxidative stress [ 33 ]. As a limitation of this study, further studies are required on the signaling mechanism of Nrf2/HO-1 [ 34 ] and the mechanism of mitochondrial protection, and external toxic brain injury models and treatment animal experiments are also needed [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that NAC has a protective effect against oxidative damage by regulating the Nrf2/HO-1 signal activated by oxidative stress [ 33 ]. As a limitation of this study, further studies are required on the signaling mechanism of Nrf2/HO-1 [ 34 ] and the mechanism of mitochondrial protection, and external toxic brain injury models and treatment animal experiments are also needed [ 35 ].…”
Section: Discussionmentioning
confidence: 99%